Working PeopleSmart : 6 strategies for success - Silberman, Melvin L. (Berrett-Koehler, 2004)
Bringing out the best in others is good business. When we bring both respect and interpersonal savvy to our work relationships, we do more than make people feel good. We enhance personal and organizational performance. And as the workplace grows more complex and competitive, managing our work relationships becomes even more essential and difficult. Now more than ever we need to work people smart. Working PeopleSmart describes the six core strategies used by people-smart individuals and shows how to apply them in the toughest workplace situations. Individuals who are people smart know how to op.
Includes index.
Keywords: Psychology, Industrial -- Handbooks, manuals, etc.; Success in business -- Handbooks, manuals, etc.; Interpersonal relations -- Handbooks, manuals, etc.; Organizational effectiveness -- Handbooks, manuals, etc.; Psychologie du travail -- Guides, manuels, etc.; Succès dans les affaires -- Guides, manuels, etc.; Efficacité organisationnelle -- Guides, manuels, etc.; BUSINESS & ECONOMICS -- Mentoring & Coaching.; BUSINESS & ECONOMICS -- Motivational.; Interpersonal relations; Organizational effectiveness; Psychology, Industrial; Success in business; Interpersoonlijke relaties.; Arbeids- en organisatiepsychologie.; Sociale beïnvloeding.; Organisatiegedrag.; handbooks.; Handbooks and manuals; Handbooks and manuals.; Guides et manuels.